Dialysis arthropathy: amyloid or iron?. Issue 6559 (29th November 1986) - Cary, N R; Sethi, D; Brown, E A; Erhardt, C C; Woodrow, D F; Gower, P E
Abstract : The clinical, biochemical, radiological, and pathological features in five cases of dialysis arthropathy were analysed. All patients were receiving long term haemodialysis and had had multiple blood transfusions. The arthropathy affected both large and small joints, was predominantly bilateral, and in all cases was associated with the carpal tunnel syndrome. In some instances joint pain was exacerbated during dialysis. In four cases the serum ferritin concentration was raised. Radiological examination showed a few juxta-articular cysts and erosions but most affected joints looked normal. All synovial tissue examined showed amyloid, which stained immunohistochemically for beta 2 microglobulin. Large amounts of iron were present in synovial tissue from affected joints. It is suggested that the deposits of iron, rather than amyloid, in synovial tissue may be the cause of the arthropathy. Iron may be derived locally as a result of haemarthrosis or it may be a manifestation of systemic iron overload.